Significant overestimation of black carbon concentration caused by high organic carbon in aerosols of the Tibetan Plateau. (1st February 2023) - Hu, Zhaofu; Kang, Shichang; Xu, Jianzhong; Zhang, Chao; Li, Xiaofei; Yan, Fangping; Zhang, Yulan; Chen, Pengfei; Li, Chaoliu
Abstract: Black carbon plays an important role in climate change. Whereas, accurate measurement of black carbon (also known as elemental carbon (EC)) is still a challenging issue because portion of the pyrolytic carbon produced from the organic carbon (OC) can cause the overestimation of EC when measured by thermal-optical method. As one of the remote regions in the world, the Tibetan Plateau (TP) is characterized as high OC/EC ratio in its atmosphere. In this study, potential influence of relative high OC concentration to EC were investigated at three remote sites (Yaze, Everest and Nam Co) in the TP. The results showed that carbonaceous aerosols from different sources can affect the fraction of OC extracted by methanol. Concentration of OC extracted by methanol had a significantly positive correlation with the reduction of pyrolytic carbon and EC concentrations, indicating that part of OC extracted by methanol can decrease the production of pyrolytic carbon and then reduce the overestimation of EC. After considering this effect, it is shown in this study that actual EC concentration at Yaze, Everest and Nam Co were overestimated by approximately 40.0 ± 12.6%, 28.8 ± 9.1% and 24.8 ± 4.7%, respectively. Accordingly, combined with the overestimation of EC concentration by carbonates, actual ratios of solar energy absorbed by organic carbon to EC were 1.67, 2.33 and 2.78 times those of original ones at Yaze, Everest and Nam Co, respectively. Therefore, warming effect caused by EC on the TP should be lower than that previously estimated. This phenomenon needs to be considered for both in situ study and model simulation in the future. Graphical abstract: Image 1 Highlights: Overestimation of EC concentration by OC in aerosols of the TP were investigated. Fraction of OC extracted by methanol was affected by the sources of aerosols. EC concentration overestimated by OC of aerosols at Yaze was up to 40.0%. Fraction of solar energy absorbed by OC relative to EC was underestimated.